2015
DOI: 10.1038/pr.2015.4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inhaled nitric oxide on white matter damage in growth-restricted neonatal rats

Abstract: This study provides new evidence that iNO could be effective in preventing brain damage and/or enhancing repair of the developing brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 38 publications
5
42
0
Order By: Relevance
“…These abnormal patterns may reflect abnormal neuronal activity and myelination and therefore abnormal functionality in the IUGR brain. These abnormal neuronal and/or white matter patterns have also been demonstrated in small animal models of IUGR (Wixey et al, 2016) with loss of oligodendrocytes, decreased proliferation and differentiation reported (Mazur et al, 2010;Olivier et al, 2005;Pham et al, 2015;Tolcos et al, 2011). Yet some studies show postnatal restoration of white matter (Olivier et al, 2007;Reid et al, 2012;Tolcos et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…These abnormal patterns may reflect abnormal neuronal activity and myelination and therefore abnormal functionality in the IUGR brain. These abnormal neuronal and/or white matter patterns have also been demonstrated in small animal models of IUGR (Wixey et al, 2016) with loss of oligodendrocytes, decreased proliferation and differentiation reported (Mazur et al, 2010;Olivier et al, 2005;Pham et al, 2015;Tolcos et al, 2011). Yet some studies show postnatal restoration of white matter (Olivier et al, 2007;Reid et al, 2012;Tolcos et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…On imaging, the FGR infant brain shows reduced total brain volume and grey matter volume [11] , and reduced hippocampal and cerebellar volume [13][14][15][16] , which might be contributed by neuronal cell loss [17] or delayed cellular complexity. Animal models of FGR, predominantly late-onset FGR, demonstrate white matter deficits as evidenced by delayed myelination [18,19] , hypomyelination, and reduced total white matter volume [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Sildenafil also reduced apoptosis, astrocytosis, and microgliosis [285]. Additionally, it has been shown that inhaling NO antagonizes hyperoxia-induced white matter damage, mitigates induced-stroke-associated brain damage, enhances CNS myelination, and promotes neural progenitor proliferation in various neonatal models [285,286,287,288,289]. …”
Section: The Utility Of Pde Inhibitors For Neuroprotection and Neumentioning
confidence: 99%